2022
DOI: 10.1021/acs.inorgchem.2c01363
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Magnetic Properties of K2Pd4U6S17, K2Pt4U6S17, Rb2Pt4U6S17, and Cs2Pt4U6S17 Synthesized Using the Boron–Chalcogen Mixture Method

Abstract: A series of A2M4U6S17 (A = alkali metal; M = Pd, Pt) compounds, specifically K2Pd4U6S17, K2Pt4U6S17, Rb2Pt4U6S17, and Cs2Pt4U6S17, were synthesized using the combined boron–chalcogen mixture and molten flux crystal growth methods. The formation of rubidium- and cesium-containing analogues resulted from a in situ alkali polysulfide flux formed from alkali carbonates. The successful synthesis of single crystals of the title compounds allowed for their structural characterization by single-crystal X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…79 They obtained novel lanthanide and actinide chalcogenides by coupling the BCM method with flux crystal growth (Figure 7). 29,79,86,87 As a continuous study, the zur Loye group evaluated the BCM method for flux crystal growth of transuranium chalcogenides and synthesized single crystals of NaCuNpS 3 . 29 For the first time, a transuranium chalcogenide was obtained using NpO 2 instead of Np metal as a starting reagent, which creates a convenient route for synthesizing novel transuranium chalcogenide materials.…”
Section: Chalcogenides Materialsmentioning
confidence: 99%
“…79 They obtained novel lanthanide and actinide chalcogenides by coupling the BCM method with flux crystal growth (Figure 7). 29,79,86,87 As a continuous study, the zur Loye group evaluated the BCM method for flux crystal growth of transuranium chalcogenides and synthesized single crystals of NaCuNpS 3 . 29 For the first time, a transuranium chalcogenide was obtained using NpO 2 instead of Np metal as a starting reagent, which creates a convenient route for synthesizing novel transuranium chalcogenide materials.…”
Section: Chalcogenides Materialsmentioning
confidence: 99%
“…The zur Loye group has addressed this issue by employing the boron chalcogen mixture (BCM) method, which provides a straightforward route for synthesizing mixed metal chalcogenides starting from metal oxide precursors. Many lanthanides and actinides containing chalcogenides, including thiophosphates and thiosilicates, were previously reported synthesized using the BCM synthesis route. Despite the existence of several reported series of thiosilicates, there remains significant room for the exploration of additional structural families and compositions, which is made possible by the thiosilicates’ extensive structural flexibility. Recently, the zur Loye group reported on two series of quaternary thiosilicates (RE 3 Mg 0.5 SiS 7 and RE 3 TM 0.5 SiS 7 ), , a class of chalcometallates synthesized via the BCM method. During the synthesis of the RE 3 Mg 0.5 SiS 7 series, we observed the presence of a trace secondary phase, identified as CaCe 2 Si 2 S 8 , where calcium originated from the flux used for crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Mesbah et al have discovered many 2H-perovskite related uranium sulfides and selenides and reported on their synthesis and characterization. The magnetic behavior of the reported compounds, however, could not be determined due to side products and UOQ (Q = S, Se) impurities that could not be separated from the reaction products, which complicates magnetic measurements. , Our group recently developed the boron–chalcogen mixture (BCM) method for actinides, and has used this method to obtain a multitude of actinide containing chalcogenides. The success of this method prompted us to expand the method toward the system of 2H-perovskite-related uranium sulfides to resynthesize some known compounds, to explore their magnetic behaviors, as well as to synthesize new compositions to add to the limited number of existing compounds. Herein, we report on the synthesis and magnetic behavior of two known 2H-perovskite-related uranium chalcogenides with the formula Ba 3 MUS 6 (M = Mn, Fe), as well as on the synthesis and characterization of three new additions to the family, Ba 3 NiUS 6 , Ba 3 CoUS 6 , and Ba 3 Co 0.858(5) Mg 0.142(5) US 6 , including the magnetic behavior of Ba 3 NiUS 6 .…”
Section: Introductionmentioning
confidence: 99%